Analysis of Wireless Power Transfer on the inductive coupling resonant - Cik Ku Haroswati Che Ku Yahaya; Syed Farid Syed Adnan; Murizah Kassim; Ruhani Ab Rahman; Mohamad Fazrul bin Rusdi (Institute of Advanced Engineering and Science, 2018)
Wireless power transfer through inductive coupling is proposed in this paper. Based on the concept of Tesla, the circuit was designed using two parallel inductors that are mutually coupled. The designed was split into two which are transmitter part and receiver part. The circuit was simulated using proteus simulation software. The results had shown that the changes in a number of turn of the inductor coils and distance of the two resonators affecting the efficiency of the power transfer. The wireless power transfer can be described as the transmission of electrical energy from the power source to the electrical load without any current-carrying wire connecting them. Wireless power transfer is deemed to be very useful in some circumstances where connecting wires are inconvenient. Wireless power transfer problems are different from wireless telecommunications such as radio. Commonly, wireless power transfers are conducted using an inductive coupling and followed by magnetic induction characteristics. In this project, we use magnetic induction using copper wire with a different diameter. By using these different diameters of wires, we are going to see the power transfer performance of each wire. It is possible to achieve wireless power transfer up to 30 centimeters between the transmitter and the receiver with a higher number of coil's turn. As concern as it may seem, the wireless power transfer field would be in high demand for electric power to be supplied in the future.